Psychological support improves outcomes of critically ill patients - Papathanassoglou, Elizabeth (My University, 2010)
Because of the hormonal, inflammatory and neuroendocrine responses they elicit, stress and negative emotions are potent pathogenetic factors in critical illness and are linked to increased morbidity and mortality. Research evidence shows that psychological support intervention, including guided relaxation and imagery techniques, can result in significant improvements in patient outcomes, vital signs and decrease pain, anxiety, complications and length of stay. Therefore, support interventions in critical care need to be investigated and in future should be vigorously implemented.
Keywords: Hearing Protector; Intensive Care Unit; Slow Wave Sleep